Validation of Genetic Markers Associated to Oxygen Availability in Low-Grade Copper Bioleaching Systems: An Industrial Application - Cortés, Mayra; Marín, Sabrina; Galleguillos, Pedro; Cautivo, Dina; Demergasso, Cecilia (Frontiers in Microbiology, 2019)
Forced aeration is one of the major energy consumption factors of the bioleaching process of run-of-mine ore. The effect of aeration in the microbial community has scarcely been studied at industrial level. Leptospirillum ferriphilum is one of the most representative components of the Fe3+ producing population in this kind of systems. We analyzed the effect of oxygen availability on L. ferriphilum by growth activity and transcriptional dynamics of its two terminal oxidases (cbb3 and bd complex) under different experimental test: culture reactor, bioleaching column and industrial heap tests. Relatively low O2 availability triggered important changes in the microbial community composition, cell growth, microbial activity and cydAB genes transcription in all cases of study. We assessed the potential role of the terminal oxidases on the adaptation to variable aeration conditions in different lifestyles of L. ferriphilum and identified transcriptional markers associated to oxygen metabolism in an industrial system. An interesting hypothesis about the possible role of cbb3 complex in the response to oxidative stress as well as their role as a high oxygen-affinity oxidase in L. ferriphilum is proposed and discussed. The results showed cydAB genes as valid genetic markers for low-grade copper industrial bioleaching systems.